CTA publishes books on successful development projects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Perimetres irrigues villageois en Afrique sahelienne by J Hecq and F Dugauquier, CTA